Hope: Claremont Studies in Philosophy of Religion, Conference 2014 - Dalferth, Ingolf U.; Block, Marlene A. (Religion in philosophy and theology, 2016)
Hope is a fundamental but controversial human phenomenon. For some it is Pandora's most mischievous evil, for others it is a divine gift and one of the highest human virtues. It is difficult to pin down but its traces seem to be present everywhere in human life and practice. Christianity as a comprehensive practice of hope cannot be imagined without it: Christians are not believers in dogmas but practitioners of hope. In other religious traditions the topic of hope is virtually absent or even critically rejected and opposed. Half a century ago hope was at the center of attention in philosophy and theology. However, in recent years the discussion has shifted to positive psychology and psychotherapy, utopian studies and cultural anthropology, politics and economics. This has opened up interesting new vistas